Tari Membantu Anak Mengekspresikan Perasaan - Annisa Zakia Nasution; Juraidah br. Sembiring; Rafiqah Hayati; Hilda Zahra Lubis (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
Dance is an effective medium for children, providing an alternative channel for expressing complex emotions and feelings. The body movements, rhythms and music of dance allow children to convey their experiences in a creative and non-verbal way. There is a positive correlation between participation in dance activities and participation in dance activities with increased social emotional development of children. By learning movement and improvisation, children can express a range of calming emotions from joy to sadness and from anger. Dance also helps children develop motor skills, coordination and creativity. Therefore, the integration of early childhood education and dance into elementary schools is highly recommended as a holistic approach to the development of children's potential and as a way to support child emotional well-being.